2020
DOI: 10.1177/1708538120923886
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carvedilol on arteriovenous graft primary patency

Abstract: Background The major mechanisms of arteriovenous graft (AVG) failure due to intimal hyperplasia (IH) are smooth muscle cell proliferation and inflammation. Therefore, carvedilol may improve AVG primary patency because of its anti-proliferative and anti-inflammatory activities. Methods The data of end-stage renal disease patients receiving regular hemodialysis were collected from the National Health Insurance Research database. The end point was the first percutaneous transluminal angioplasty (PTA) for AVG fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
2
0
1
Order By: Relevance
“…11,14 However, previous reports have found that smoking is not significantly associated with reductions in AVG primary and secondary patency rates. 19,20 This phenomenon could be attributed to the relative rates of diabetes between these reports and our study. These reports display a diabetic incidence of 70% 19,20 whereas this study has a relatively lower reported incidence (Table 1).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…11,14 However, previous reports have found that smoking is not significantly associated with reductions in AVG primary and secondary patency rates. 19,20 This phenomenon could be attributed to the relative rates of diabetes between these reports and our study. These reports display a diabetic incidence of 70% 19,20 whereas this study has a relatively lower reported incidence (Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…19,20 This phenomenon could be attributed to the relative rates of diabetes between these reports and our study. These reports display a diabetic incidence of 70% 19,20 whereas this study has a relatively lower reported incidence (Table 1). Diabetic patients have an increased risk of neointimal hyperplasia due to platelet hyperactivity which stimulate vascular smooth muscle cells to proliferate.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation